Impact of the COVID-19 pandemic on the Andalusian program for early detection of diabetic retinopathy: a population-based study - Ravé Garcia, Reyes; Rodríguez de Vera Gómez, Pablo; Mayoral Sánchez, Eduardo; Aguilar Diosdado, Manuel; Martínez-Brocca, María Asunción (Frontiers in Clinical Diabetes and Healthcare, 2025)
AimsTo analyze the impact of the COVID-19 pandemic on the activity and outcomes of the Andalusian Program for Early Detection of Diabetic Retinopathy (APDR).MethodsA retrospective observational study was conducted during 2018–2023. The following variables were analyzed annually: newly included patients, retinal photographs performed, and pathological findings categorized by severity. Moderate-to-severe non-proliferative and proliferative retinopathy were classified as vision-threatening diabetic retinopathy (VTDR).ResultsIn 2020 and 2021, the number of newly included patients (11,897 and 18,343, respectively) and retinal photographs performed (39,667 and 64,092, respectively) decreased compared to previous years (2018 and 2019: 25,940 and 30,807 new patients, respectively; 85,171 and 100,849 retinal photographs, respectively). In 2022, activity levels increased 160% compared to 2019. The proportion of VTDR cases remained stable at 0.163%, 0.14%, and 0.075% during 2021, 2022, and 2023, respectively, compared to the prepandemic period (0.168% and 0.117% in 2018 and 2019, respectively).ConclusionsDespite the slowdown in activity during the COVID-19 pandemic, the post-pandemic proportion of VTDR cases diagnosed through the APDR remained stable, suggesting resilience against severe outcomes despite healthcare disruption. The program has demonstrated an effective recovery. Ongoing long-term monitoring is essential to fully assess the pandemic’s potential impact on late-stage complications.